Risk Factors for Primary Bone Cancer After Childhood Cancer: A PanCare Childhood and Adolescent Cancer Survivor Care and Follow-Up Studies Nested Case-Control Study - Reulen, Raoul C.; Winter, David L.; Diallo, Ibrahim; Veres, Cristina; Llanas, Damien; Allodji, Rodrigue S.; Bagnasco, Francesca; Bárdi, Edit; Feijen, Elizabeth A.M.; Alessi, Daniela; Fidler-Benaoudia, Miranda M.; Høgsholt, Stine; et al. (Journal of clinical oncology, 2023)
PURPOSERadiation to the bone and exposure to alkylating agents increases the risk of bone cancer among survivors of childhood cancer, but there is uncertainty regarding the risks of bone tissue radiation doses below 10 Gy and the dose-response relationship for specific types of chemotherapy.METHODSTwelve European countries contributed 228 cases and 228 matched controls to a nested case-control study within a cohort of 69,460 5-year survivors of childhood cancer. Odds ratios (ORs) of developing bone cancer for different levels of cumulative radiation exposure and cumulative doses of specific types of chemotherapy were calculated. Excess ORs were calculated to investigate the shape and extent of any dose-response relationship.RESULTSThe OR associated with bone tissue exposed to 1-4 Gy was 4.8-fold (95% CI, 1.2 to 19.6) and to 5-9 Gy was 9.6-fold (95% CI, 2.4 to 37.4) compared with unexposed bone tissue. The OR increased linearly with increasing dose of radiation (Ptrend < .001) up to 78-fold (95% CI, 9.2 to 669.9) for doses of ≥40 Gy. For cumulative alkylating agent doses of 10,000-19,999 and ≥20,000 mg/m2, the radiation-adjusted ORs were 7.1 (95% CI, 2.2 to 22.8) and 8.3 (95% CI, 2.8 to 24.4), respectively, with independent contributions from each of procarbazine, ifosfamide, and cyclophosphamide. Other cytotoxics were not associated with bone cancer.CONCLUSIONTo our knowledge, we demonstrate-for the first time-that the risk of bone cancer is increased 5- to 10-fold after exposure of bone tissue to cumulative radiation doses of 1-9 Gy. Alkylating agents exceeding 10,000 mg/m2 increase the risk 7- to 8-fold, particularly following procarbazine, ifosfamide, and cyclophosphamide. These substantially elevated risks should be used to develop/update clinical follow-up guidelines and survivorship care plans.